Thermal and physical damage in skull base drilling using gas cooling modes: FEM simulation and experimental evaluation. (November 2021) - Gholampour, Seifollah; Hassanalideh, Hossein Haghighi; Gholampour, Mansore; Frim, David
Highlights: ● The FEM simulation indicated that the efficiency of CO2 gas coolants in reducing the maximum temperature, thrust force and torque was more than conventional cooling modes. ● CO2 gas coolants had minimum cracks and the slightest surface defects after skull drilling. ● The similar effect of repeated drillings on thrust force and torque was less than the temperature in all cooling modes. ● The repeated drillings did not have considerable effects on the maximum and durability of temperature in the CO2 cooling modes. ● The external CO2 gas coolant was led to an optimal skull base drilling with minimum risks of thermal and physical damages and drill bit breakage. Abstract: Background: Skull base drilling, as a high-risk process, is one of the most important techniques of skull base surgeries. Methods: The temperature, thrust force, and torque were calculated using finite element method (FEM) simulation under two conventional cooling models, and internal and external CO2 cooling modes at four rotational speeds (1000–4000 rpm). The temperatures at the bottom and on the surface of the drilling site were measured experimentally using a thermometer and a thermographic camera, respectively. The results were then compared with FEM results. Results: The efficiency rates of CO2 coolants in reducing the maximum temperature, thrust force, and torque were at least 5.0–11.2%, 16.5–33.8%, and 6.9–11.3% higher than conventional cooling modes, respectively. The experimental results indicated that, in contrast to the maximum temperature, temperature durability was 72.7–107.3% higher in the conventional cooling modes than the cooling modes with external CO2 coolant systems. The cracks and surface defects were less in the CO2 coolants than the other cooling modes. The maximum temperature after the second and third drillings increased by 17.7 and 26.8%, compared to the first drilling in the conventional cooling modes. On the other hand, the repeated drillings had no impact on the temperature in the CO2 cooling modes. Conclusion: Skull base drilling with a rotational speed of 2000 rpm in the cooling mode of an external CO2 coolant, even for repeated drillings, can lead to a skull drilling process with minimum risk of drill bit breakage and thermal and physical damage.